SOSIALISASI TENTANG PEDOMAN TEKNIS PERATURAN DI DESA PADA PEMERINTAH DESA ULAK KERBAU LAMAKECAMATAN TANJUNG RAJA KABUPATEN OGAN ILIR - Lisa Mandasari; Dian Anggraini, Riza Adelia Suryani (JOURNAL OF COMMUNITY DEDICATION, 2023)
The paradigm shift in Indonesia's government system during the current era of reform, transitioning from a centralized to a decentralized system, has implications for changes in regional development management systems. This includes matters related to the creation and establishment of regulations at the village level. The objective is to empower villages to align their specific needs with their local regulations, fostering a strong synergy between the regulations they set and the developmental requirements of the village. In the context of Law Number 111 of 2014 regarding the technical guidelines for regulations in villages during the process of forming legal products, there are several aspects that need attention. These considerations are briefly based on specific principles outlined in legislation. These points serve as the foundation for the outreach activities, given the limited understanding among village governments regarding the technical aspects of forming village regulations. The community outreach initiative took place in Ulak Kerbau Lama Village, Tanjung Raja Subdistrict, Ogan Ilir Regency. The village government, consisting of village leaders and officials, the Village Consultative Body, and community leaders, who are the primary targets of this outreach activity, actively participated in its implementation. The high enthusiasm of the participants is evident from the numerous questions posed by village officials.